2011
DOI: 10.1007/s11517-011-0820-5
|View full text |Cite
|
Sign up to set email alerts
|

Design of a novel mobility device controlled by the feet motion of a standing child: a feasibility study

Abstract: Self-generated mobility is a major contributor to the physical, emotional, cognitive, and social development of infants and toddlers. When young children have disorders that hinder self locomotion, their development is at risk for delay. Independent mobility via traditional power mobility devices may prevent this delay, but do little to encourage the child's development of gross motor skills. This research aims to develop a bio-driven mobile-assistive device that is controlled and driven by moving the feet, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…. limit 6 to ("newborn infant (birth to 1 month)" or "infant (1 to 23 months)" or "preschool child (2 to 5 years)" or "child (6 to 12 years)" or "adolescent (13 to 18 years)" or "young adult (19 to 24 years)" 12 Jone et al, 13 Jones et al, 14 Tefft et al, 15 Huang et al, 17 Bottos et al, 23 Bamer et al, 55 Galloway et al, 57 Pritchard-Wiart et al, 58 Evans et al, 59 Feldner et al, 60 Kenyon et al, 61 Evans and Baines, 62 Furumasu et al, 81 Logan et al, 87 Butler, 89 Cooper et al, 168 Huang and Galloway, 169 Kornafel et al, 104 Logan et al, 90,118 Mockler et al, 111 Odor and Watson, 91 Pope et al, 125 Smania et al, 123 Stokes et al, 92 Uyama and Hanaki, 112 Zazula and Foulds, 119 Durkin, 109 Gudgeon and Kirk, 99 Pituch et al, 100 Sonday and Gretschel, 101 Wiart et al, 102 Currier et al, 105 Feldner, 116 Home and Ham, 106 Huhn et al, 130 Kakimoto et al, 107 Lovett, 113 Omori et al, 114 Schoepflin et al, 128 Weinstein et al, 93 Larin et al,…”
Section: Acknowledgementsmentioning
confidence: 99%
“…. limit 6 to ("newborn infant (birth to 1 month)" or "infant (1 to 23 months)" or "preschool child (2 to 5 years)" or "child (6 to 12 years)" or "adolescent (13 to 18 years)" or "young adult (19 to 24 years)" 12 Jone et al, 13 Jones et al, 14 Tefft et al, 15 Huang et al, 17 Bottos et al, 23 Bamer et al, 55 Galloway et al, 57 Pritchard-Wiart et al, 58 Evans et al, 59 Feldner et al, 60 Kenyon et al, 61 Evans and Baines, 62 Furumasu et al, 81 Logan et al, 87 Butler, 89 Cooper et al, 168 Huang and Galloway, 169 Kornafel et al, 104 Logan et al, 90,118 Mockler et al, 111 Odor and Watson, 91 Pope et al, 125 Smania et al, 123 Stokes et al, 92 Uyama and Hanaki, 112 Zazula and Foulds, 119 Durkin, 109 Gudgeon and Kirk, 99 Pituch et al, 100 Sonday and Gretschel, 101 Wiart et al, 102 Currier et al, 105 Feldner, 116 Home and Ham, 106 Huhn et al, 130 Kakimoto et al, 107 Lovett, 113 Omori et al, 114 Schoepflin et al, 128 Weinstein et al, 93 Larin et al,…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The clinical results on the case studies on Johnson [9] showed that stroke patients compared to healthy subjects move slower and are less likely to use their arm simultaneously even when the functional task requires simultaneous movement. Pradhan [14] also presents an interesting clinical research that tries to examine the effects of medication on the attentional demands of precision and power grips in individuals with Parkinson disease.…”
mentioning
confidence: 99%